Soil ecological zoning in the middle Volga region using GIS technologies. Issue 1 (October 2021) - Antropov, D V; Chursin, A I; Konokotin, D N; Salov, S M; Samoylenko, D V
Abstract: The article examines the issue of soil ecological zoning of territories. GIS technologies used for the soil-ecological zoning are described. A new type of soil-ecological zoning of the Middle Volga region by means of GIS technologies is presented. It is in compliance with the current state of the soil cover, erosion processes and the agricultural land structure in the region.